Pengembangan Bahan Ajar Digital Teks Cerita Fantasi Bermuatan Nilai-Nilai Moral - Rahmawati Rahmawati; Ratna Dewi Kartikasari (Journal on Education, 2023)
This study aims to develop digital teaching materials with fantasy story text material with moral values to make it easier for students to understand the material and increase the moral values contained in them. In this study, the writer developed digital teaching materials using the Research and Development (R&D) method of the ADDIE model which consists of: 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. The data obtained in this study were obtained using data collection techniques in the form of observations, interviews, giving questionnaires to students and teachers, as well as material experts and media experts to determine the feasibility of digital teaching materials that have been developed. The results of this study indicate that digital teaching materials for fantasy story texts with moral values get very feasible criteria for use. This can be seen based on the assessment of media experts of 97% and 96% based on the assessment of teaching material experts. Meanwhile, the results of the assessment of digital teaching materials by Indonesian language teachers obtained a feasibility percentage of 91% and the results of student responds to the digital teaching materials got a percentage of 90%. Digital teaching materials for fantasy story texts with moral values can be used by teachers and grade VII students in Indonesian language learning activities.